Perwujudan Kesantunan Berbahasa Jawa dalam Interaksi antara Dosen dan Mahasiswa di Prodi Pendidikan Bahasa Jawa - Ajeng Rahadini, Astiana; Dwi Lestari, Winda (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2024)
Language politeness is important in the communication process. Language politeness will make speakers and speech partners comfortable communicating so that the purpose of communication can be achieved. Javanese language has its own politeness parameter. This study aims to describe the form of Javanese language politeness between lecturers and students in the Javanese Language Education study program at FKIP Sebelas Maret University and the causes of the emergence of language impoliteness. The research method used is descriptive qualitative with observation technique. The data used are speeches between lecturers and students in academic activities in the Javanese Language Education Study Program FKIP UNS. The research was conducted for one semester with the object of the research being students of semester I, III, V, and VII in 2023. The results showed that: 1) The form of politeness in Javanese language of lecturers is represented in declarative mode or in the form of news sentences, interrogative mode or in the form of question sentences, and imperative mode or in the form of command sentences which represent the types of representative, directive, expressive, and commissive speech acts. Meanwhile, the students' Javanese politeness is represented in declarative mode or news sentences, interrogative mode or question sentences, and imperative mode or command sentences that represent the types of directive and expressive speech acts. In addition, the use of ngoko alus is also used in the lecturer's speech to students as a form of respect while the Javanese language used by students to lecturers is krama inggil. 2) The level of language politeness of students to lecturers is influenced by factors of understanding of Javanese ethics and mastery of the maxims of Javanese politeness, especially mastery of Javanese language.